Laparoscopic temporary bilateral uterine artery occlusion with silicone tubing to prevent hemorrhage during vacuum aspiration of cesarean scar pregnancies. Issue 11 (14th July 2015) - Wang, Lingling; Sun, Lingbin; Wang, Lijun; Chen, Huifang; Ouyang, Xue; Qiu, Huiling
Abstract: Aim: The aim of this study was to determine the feasibility and effects of temporary bilateral uterine artery occlusion with silicone tubing on blood loss during vacuum aspiration of cesarean scar pregnancies (CSP). Material and Methods: Six patients with CSP underwent removal of gestational masses via vacuum aspiration. At the beginning of the procedure, all patients underwent laparoscopic temporary bilateral uterine artery occlusion with tubing. The main measurements were the operating time, operative blood loss, Doppler examination of the uterine arteries, and complications of procedure. Results: The median operation time was 99 min, the median time needed to put the tubing in place (the time from the opening of the retroperitoneum to positioning of the tubing) was 45.5 min and the median time of bilateral uterine artery occlusion with tubing was 32.5 min. The median blood loss was 97.5 mL, and none of the patients required blood transfusion. Doppler examination showed no difference in the pre‐ and postoperative resistance or pulsatility indices of the uterine vessels. There were no conspicuous complications. The serum ß‐human chorionic gonadotrophin level decreased to normal within 14–27 days after the operation. Conclusion: Laparoscopic temporary bilateral uterine artery occlusion with silicone tubing is an effective, minimally invasive procedure for reducing blood loss during vacuum aspiration in patients with CSP.